Perancangan Interior ―Bambini‖ Day Care Centre di Surabaya - Azarine Devina Gunawan; mariana wibowo (Intra, 2016)
Surabaya has many career women. Some of these career women work all day so they are forced to entrust their children to the third party. Children between age 0-5 years experience Golden age periode. Children brains grow rapidly in this period. It will be a waste if the third party who handled these children is irresponsible so the development of children’s brain won’t be maximum. Day care could be the answer for the parents to take care of their children while they’re working. Day care will be designed with fun and ergonomic design that match the corporate identity of Bambini. This day care concept project is “Funtastic”. The design will use cheerful color such as white, blue, yellow, green, and white. This concept is choosen in order to make children happy and enjoy when they do their activities. These feelings make the children easier to receive educational material, so golden age periode can be maximized.